Question
Asked Dec 9, 2019
16 views
For the given functions f and g, complete parts (a)-(h). For parts (a)-(d), also find the domain.
f(x) = 4 +
х
; g(x):
х
(a) Find (f + g)(x).
(f + g)(x) =
(Simplify your answer.)
help_outline

Image Transcriptionclose

For the given functions f and g, complete parts (a)-(h). For parts (a)-(d), also find the domain. f(x) = 4 + х ; g(x): х (a) Find (f + g)(x). (f + g)(x) = (Simplify your answer.)

fullscreen
check_circle

Expert Answer

Step 1

Given functions f and g are

help_outline

Image Transcriptionclose

f (x) = 4+- g(x) =-

fullscreen
Step 2

(a)

(f + g)(x) can be written as

help_outline

Image Transcriptionclose

(f +g)(x) = f(x)+g(x)

fullscreen
Step 3

Therefore,

&nb...

help_outline

Image Transcriptionclose

(f + g)(x) = f(x)+g(x) -(+-)-() - 7+7 = 4+- 14 = 4+

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Other